1996
DOI: 10.1007/bf01969732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold exposure on electrophysiological properties of rat heart

Abstract: Male rats exposed to the cold (4 degrees C) for five or ten days exhibited modifications in their thyroid state, as documented by increases in serum thyroid hormone levels, to which differently graded modifications of heart weight/body weight ratio, heart rate, and resting metabolic rate were associated. The values of the above mentioned thyroid state indicators returned to those of the control when the animals, kept at cold for ten days, were re-exposed to room temperature (24 degrees C) for an additional 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This idea seemed to be supported by the observation that the extent of oxidative damage found following thyroid hormone treatment [7], cold exposure [77], exercise [77] and caloric restriction [78] was related to the organism's metabolic state. In effect, the hyperthyroid functional state induced in mammals by cold exposure, like experimental hyperthyroidism, leads to enhancement of their basal metabolic rate [79], which reflects increases in the cellular respiration of target tissues as BAT [77], liver, and cardiac and skeletal muscles [80]. However, a recent report has shown that during both pyruvate/malate and succinate-supported state 4 respiration, H 2 O 2 generation by liver mitochondria from cold-exposed rats is accelerated without any change in the O 2 consumption rate [81].…”
Section: Biochemical Changes Determining Increased Ros Productionmentioning
confidence: 98%
“…This idea seemed to be supported by the observation that the extent of oxidative damage found following thyroid hormone treatment [7], cold exposure [77], exercise [77] and caloric restriction [78] was related to the organism's metabolic state. In effect, the hyperthyroid functional state induced in mammals by cold exposure, like experimental hyperthyroidism, leads to enhancement of their basal metabolic rate [79], which reflects increases in the cellular respiration of target tissues as BAT [77], liver, and cardiac and skeletal muscles [80]. However, a recent report has shown that during both pyruvate/malate and succinate-supported state 4 respiration, H 2 O 2 generation by liver mitochondria from cold-exposed rats is accelerated without any change in the O 2 consumption rate [81].…”
Section: Biochemical Changes Determining Increased Ros Productionmentioning
confidence: 98%
“…Thyroid hormone-mediated processes are elevated during long-term cold exposure appearing as a hyperthyroid state. Venditti and colleagues have shown that the hyperthyroid functional state induced in mammals by cold exposure, like experimental hyperthyroidism, led to enhancement of their basal metabolic rate, which reflects an increase in the cellular respiration of target tissues including BAT, liver and cardiac and skeletal muscles (35,99,100). There are data indicating that in hyperthyroid tissues increased ROS and RNS production, as well as the decrease in antioxidant capacity and susceptibility to oxidative damage occurs (101).…”
Section: Long-term Cold Exposurementioning
confidence: 99%